An Examination of the Impact of Mobile Technology on Quality of Education in a Large Public School in Mozambique - O'SULLIVAN, MARY LINDA (Trinity College Dublin. School of Education. Discipline of Education, 2019)
This study was carried out in parallel with a wider study on the impact of the introduction of a mobile technology project, IADT s School in a Box, on the quality of education in a large public school in Mozambique. The study is grounded in Sustainable Development Goal 4: ensure inclusive and equitable quality education and promote lifelong learning opportunities for all (United Nations, 2015). In particular, this thesis focuses on the role of teachers in the achievement of the goal, examining how mobile technology can be a catalyst for changing teaching practice toward a more collaborative and creative approach, and how teachers can support each other s improving practice through a community of practice. The study used a developmental research approach over thirteen months, mediated by the Irish Embassy in Mozambique. During this time the researcher visited Mozambique four times carrying out field research, deploying the technology and developing and co-ordinating eleven days of teacher workshops over this period. Ten teachers from the school, all teaching third grade, took part in the teacher workshops, five of those taught using the technology, and five did not use the technology in their classes over this time period. The use of the technology by teachers was examined using a Cultural Historical Activity Theory (Vygotsky, 1978; Engeström, 1987) framework, implementing changes in practice in step-by-step approach, within the socio-cultural context of the school. The outcome of teachers changing competence was examined within the TPACK Framework (Koehler & Mishra, 2009). Findings showed that even within very complex and challenging contexts, that a holistic step-by-step approach to change in teaching practice, did lead to teachers growing competence in collaborative and creative teaching practices using mobile technology in a whole class teaching approach.
APPROVED
Keywords: Teaching Sub Saharan Africa; Creative Teaching; Participative Teaching; Sustainable Development Goal 4; Educational Development; Community of Practice Education; Educational Technology